‎“TOPOGRAPHY OF THE THYROID GLAND, ITS BLOOD SUPPLY AND HISTOLOGICAL STRUCTURE IN ONE ‎HUMPED CAMEL” (CAMELUS DROMEDERIUS).‎ - Y . D. Al-Fayaz, J .; S. Al-Samarrae, N.; A.H. Al-‎ Nuaini‎, K. (The Iraqi Journal of Veterinary Medicine, 2024)
The thyroid gland of Camelus dromedrius is located directly behind the larynx. It consists of two lateral lobes at the sides of trachea. The lobes are connected to each other by a caudal isthmus from the ventral surface. The lobes extend to the seventh tracheal ring and even to the eighth or ninth ring. The medial surface of the lobes is adhered to trachea. The lateral surfaces are convex. Also, the dorsal and ventral edges of the lobes are convex.The thyroid gland receives blood via caudal thyroid artery and cranial thyroid artery. A third artery which is initiated from the common carotid artery serves as a medial thyroid artery.Histological observation showed that the lobes and isthmus are surrounded by an external capsule mainly of loose connective tissue and an internal capsule of dense irregular connective tissue.The follicles of the gland sometimes appear as regular follicles but other follicles are of semi tubular shape or branched.